Perencanaan dan Asesmen Perkembangan Pada Anak Usia Dini: Studi kasus pada Lembaga Pendidikan Anak Usia Dini (PAUD/TK/RA) di Daerah Istimewa Yogyakarta - Suyadi, Suyadi (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2016)
The purpose of this research is to uncover how teachers at institutions of education (PAUD/TK/RA) make the assessments and planning of the childhood development and to know the assessments process difficulties. Methods used is survey, namely by seeking information on the implementation of planning and the assessments process of the childhood development from 55 educator at educational institutions in special region of Yogyakarta. The conclusions from this study were that in make the planning evaluation all teachers have appropriate to childhood developmental tasks (STPPA). As for technique of assessments most commonly used the observation and portfolio methods, because it’s more simple and easily.